Halal Practices Integrity and Performance Relationship: Are Halal Supply Chain Trust and Commitment the Missing Links? - Kamisah Supian; Mokhtar Abdullah; Norasekin Ab Rashid (International Journal of Supply Chain Management, 2019)
Preserving the integrity of halal food has become increasingly complex since its supply chain undergo numerous production processes and distribution stages performed by different organisations. The longer the supply chain is, the greater its vulnerability and complexity. Concurrently, the rise in the number of halal food product status revocation indicates their non-compliance with Shariah requirements. As such, this study aims to investigate the influences of halal practices integrity, halal supply chain trust and halal supply chain commitment on Malaysia halal food supply chain performance. 212 questionnaires were distributed to the participants of Malaysia Halal Expo and the responses were analysed using Smart PLS. The inclusion of halal supply chain trust and halal supply chain commitment in the conceptual model revealed a complementary mediation influence on the relationship between halal practices integrity and supply chain performance. The findings of this study have significantly contributed to both theories and practices by enhancing halal integrity in the food supply chain.